Analisis Penerapan Manajemen Persediaan pada Perusahaan Goodwill - Putra, Angga Kusuma; Hongdiyanto, Charly (Jurnal Aplikasi Manajemen, 2015)
The purpose of this study is to determine the appropriate stock of managementsystem for Goodwill Company, for both present time and the next two years. This study usesStock Management Theory, Economic Order Quantity (EOQ) and Just In Time (JIT) Methods.EOQ method uses some calculations in order to know the optimum stock for a company,the total costs, and the re-order point. Meanwhile, JIT theory consists of information on howto apply the method in the company, including the advantages and disadvantages of usingthe method. The population of the data and sample were taken from the interviews conductedto the similar companies and masons which were involved in Goodwill's business. Resultsshow that the company has yet effectively apply the right stock management. Based on thecalculation that uses total cost formula, the EOQ methods will enable the company to savemore on total cost compared to the company's current stock management system. In addition,the JIT methods can make the company save even more on total cost compared to EOQmethods. However, judging from the present condition of the company, the company is not yetable to apply the JIT methods. Therefore, the future plan for the company is to apply the EOQmethods in the next year and the JIT methods in the next two years as its stock managementsystem.